2001
DOI: 10.1038/sj.cdd.4400862
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of Fas ligand on tumor cells escaping active specific immunotherapy

Abstract: Mice transgenic for the rat HER-2/neu oncogene (rNeu-TG) developed spontaneous breast tumors that can escape a rNeu-specific immune response induced by active specific immunotherapy (ASI). The ability of these escape tumors to grow appeared to be due to upregulation of the Fas ligand (Fas-L) molecule. In an effort to develop tools for the better elucidation of the role of Fas-L and other regulatory mechanisms in tumor escape, we established cell lines derived from escape tumors. These tumor cell lines retained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 36 publications
(31 reference statements)
1
6
0
Order By: Relevance
“…[13,15,16]). In agreement with this notion, we have observed that in a mouse model for mammary gland tumors, FasL-expressing tumors are persisting whereas FasL-negative tumors are eliminated by the immune system [17].…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…[13,15,16]). In agreement with this notion, we have observed that in a mouse model for mammary gland tumors, FasL-expressing tumors are persisting whereas FasL-negative tumors are eliminated by the immune system [17].…”
Section: Introductionsupporting
confidence: 81%
“…Tumor cell-expressed FasL has been thought to induce apoptosis in tumor-infiltrating cytotoxic T cells and may therefore save tumor cells from destruction by the immune system. While many studies have supported this idea [14,16,17,39,40], others have reported opposing findings [41,42]. This controversial issue has not been solved so far and the expression and the biological function of FasL in tumors probably depend on the context and cellular environment (reviewed in Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we observed a reduction of Fas expression in NIT-1 cells that had been passaged frequently and kept in culture for longer periods of times (P. Augstein, unpublished observations). Probably, surface expression of Fas in NIT-1 cells is influenced by their oncogenic transformation and could be affected by similar mechanisms that enable tumour cells to escape from cytotoxic elemination mechanisms such as downregulation of death receptors involved in apoptotic pathways (Cefai et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the pro-apoptotic function of FasL on carcinoma cells has been demonstrated in both in vitro and in vivo; in co-cultures with a variety of carcinoma cell lines, FasL expressed on carcinoma cells induce apoptosis of lymphocytes in Fas-dependent manner [49,51,62-66], and in carcinoma biopsies from patients, the present of FasL on carcinoma cells is in parallel with apoptosis of TICs [53,60,67-69] or reduced number of TICs [70,71]. In the experimental studies with animal models, down-regulation of FasL expression in carcinoma significantly reduces tumor development in syngeneic immunocompetent mice [72], while persistent expression of Fas enhances tumor growth along with an increase in lymphocyte apoptosis [73,74], and is acquired for survival from active specific immunotherapy [75]. …”
Section: Introductionmentioning
confidence: 99%